Second use or recycling of hydrogen waste gas from the semiconductor industry - Economic analysis and technical demonstration of possible pathways. (21st June 2019) - Rochlitz, L.; Steinberger, M.; Oechsner, R.; Weber, A.; Schmitz, S.; Schillinger, K.; Wolff, M.; Bayler, A.
Abstract: Hydrogen is used as a carrier gas in the photovoltaics and semiconductor industry. Once scrubbed from poisonous and environmentally harmful substances, the hydrogen-rich waste gas streams are released into the atmosphere. This paper presents an economic analysis of different options for further use of these streams. Combustion in a gas engine with attached electricity generation is currently the most technologically proven and economically profitable solution. With the future rise of the hydrogen electric vehicle infrastructure, power generation via a polymer electrolyte membrane (PEM) fuel cell system could become economically feasible at electricity prices of 0.11 €/kWh and higher. Fuel cells are high tech and modular but still relatively expensive today. Another promising technology identified is the recycling of hydrogen via electrochemical hydrogen compression (EHC). EHC is already economically feasible today at a hydrogen price of 11 €/kg or higher. It will become even more profitable with falling membrane electrode assembly prices. Highlights: First economic and technological assessment for second use of H2 -rich waste gas. Using waste gases for more profitable and more sustainable semiconductor production. Fuel cells show high future savings potential in semiconductor gas abatement. Electrochemical hydrogen compression has high future potential for gas recycling. Electrochemical hydrogen recycling can outweigh electricity generation earnings.